2013
DOI: 10.1089/ten.tea.2012.0279
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Fibrous Scaffolds for Enhanced Mechanoresponse and Tenogenesis of Mesenchymal Stem Cells

Abstract: Topographical cell guidance has been utilized as a tissue-engineering technique to produce aligned cellular orientation in the regeneration of tendon- and ligament-like tissues. Other studies have investigated the effects of dynamic culture to achieve the same end. These works have, however, been limited to two-dimensional cultures, with focus given to the effects from the stimuli independently. The understanding of their combined effects in the tenogenic differentiation of mesenchymal stem cells (MSCs) has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 44 publications
6
67
0
Order By: Relevance
“…Silk fibres functionalised with peptide moieties [377], HA [378] and chondroitin sulphate / collagen [379] have been shown to maintain tendon function in vitro, to increase blood vessel formation and cellular infiltration, to promote formation for dense collagen fibres and to encourage overall tendon healing over control counterparts in a canine patellar tendon defect model and to a rabbit cruciate ligament defect model. Mechanical loading of aligned silk scaffolds loaded with BMSCs resulted in increased production of collagen type I, collagen type III and tenascin C, when compared to not aligned and not mechanically stimulated counterparts [380]. Further large animal model studies have demonstrated that silk / BMSCs composites induced functional ACL replacement, with silk degrading in a similar rate as the neotissue was formed [381].…”
Section: Bottom-up Approached For Tendon Repair Based On Natural In Omentioning
confidence: 99%
“…Silk fibres functionalised with peptide moieties [377], HA [378] and chondroitin sulphate / collagen [379] have been shown to maintain tendon function in vitro, to increase blood vessel formation and cellular infiltration, to promote formation for dense collagen fibres and to encourage overall tendon healing over control counterparts in a canine patellar tendon defect model and to a rabbit cruciate ligament defect model. Mechanical loading of aligned silk scaffolds loaded with BMSCs resulted in increased production of collagen type I, collagen type III and tenascin C, when compared to not aligned and not mechanically stimulated counterparts [380]. Further large animal model studies have demonstrated that silk / BMSCs composites induced functional ACL replacement, with silk degrading in a similar rate as the neotissue was formed [381].…”
Section: Bottom-up Approached For Tendon Repair Based On Natural In Omentioning
confidence: 99%
“…25,26 Recently, the fibroin fibers of the B. mori mulberry silkworm have been assessed for use in tendon/ ligament regeneration. 28,29,[35][36][37][38]60,61 These silk fibers have also been used as sutures since the late 19 th century 62 and when implanted subcutaneously, B. mori silk fibroin elicits very mild immune responses. 63,64 Indeed, the majority of silk based tissue engineered constructs utilize the fibroin from B. mori, most likely due to its high availability and good mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Studies evaluating silk as a biomaterial for tendon regeneration have largely focused on the mulberry B. mori silk or composites of B. mori silk with either synthetic polymers or collagen. 28,29,[35][36][37][38] However, given that non-mulberry silks contain the cell binding RGD tripeptide motif, [39][40][41] and have been shown to support fibroblast-like and bone marrow-derived mesenchymal stem cell growth in vitro, 42,43 non-mulberry silk-derived scaffolds hold much promise as biomaterials for enhancing tendon tissue regeneration. 44 In this study, in vitro assays were used to assess the cytocompatibility and immunogenicity of a novel knitted, nonmulberry silk fibroin scaffold designed for use in tendon tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…6 Fit of the experimental equibiaxial mechanical behavior for the anisotropic scaffold (left). Predicted biaxial mechanical behavior of the isotropic scaffold (right) by using the optimal material parameters of the anisotropic scaffold contact guidance by the scaffold fibers (Niklason 2009;de Jonge 2013), enhanced collagen deposition due to scaffold anisotropy (Lee 2005;Teh et al 2013) or use of cyclic load (Boerboom et al 2008;Rubbens 2009) and load protection from enzymatic degradation (Huang and Yannas 1977;Wyatt et al 2009). It should be noticed that the described phenomena only occur when microfibrous scaffolds are used.…”
Section: Discussionmentioning
confidence: 99%
“…φ max is the maximum collagen volume fraction, which is set 0.15 [estimated as possible collagen volume fraction after 2 weeks of tissue culture from the work of Van Geemen (2012) and Mol (2005)], and φ c is the current total collagen volume fraction. The exponential of β s indicates that the scaffold anisotropy influences the amount of collagen that is produced (Lee 2005;Teh et al 2013). Furthermore, the inverse proportionality with the current radius r(γ ) and the collagen fiber length l(γ ) indicates that the volume of collagen deposited by the cells in each direction is constant at each time step.…”
Section: Microscale Growth and Degradation Modelmentioning
confidence: 99%